HEALTH CONDITONS AND HEALTHCARE UTILIZATION OF HOUSEHOLDS IN SELECTED COASTAL AREAS OF HUE CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe self-reported morbidity and the utilization of healthcare services among households in selected coastal areas of Hue City over the past 12 months. Subjects & Methods: A cross-sectional descriptive study was conducted among 200 households comprising 721 individuals. Data were collected through face-to-face interviews using a structured questionnaire in October 2025. Descriptive statistics were applied for data analysis. Results: Regarding self-reported conditions in the past 12 months, the most commonly reported acute illnesses were respiratory diseases (40.8%), musculoskeletal disorders (19.9%), and gastrointestinal diseases (14.8%). Among chronic conditions, cardiovascular diseases (39.8%), diabetes (19.5%), and chronic musculoskeletal disorders (17.1%) were the most prevalent. The proportion of individuals who utilized healthcare services within the past 12 months was 55.8%; however, 44.2% did not seek formal care, and 10.3% reported self-care or self-medication. Most participants sought care at provincial and central hospitals, while only 3.2% utilized commune health stations.  Conclusion: Self-reported morbidity and healthcare utilization patterns among households in coastal areas of Hue City indicate a substantial need for healthcare services, while access to primary healthcare remains limited. Strengthening the capacity and quality of primary healthcare services is essential to improve healthcare effectiveness and reduce the financial burden on households.
Keywords: Household; health condition; healthcare utilization; coastal area; health status